Diversity and morphological characteristics of Aspergillus species and Fusarium species isolated from cornmeal in Malaysia - Perumal, Nithiyaa; Mohd Zainudin, Nur Ain Izzati; Yusuf, Umi Kalsom; Salleh, Baharuddin (Universiti Putra Malaysia Press, 2012)
Corn is a vital food component that serves as a nutritional diet element for human and feedstuff for livestock. Despite its vast importance, corn frequently faces contamination problem caused by a range of microbes especially fungi. For the purpose of this study, cornmeal samples were collected from nine states in Malaysia, and were cultured onto Peptone Pentachloronitrobenzene Agar (PPA) to isolate the fungi. Single spore isolation was done on Potato Dextrose Agar (PDA) to obtain the pure culture. A total of 314 isolates of microscopic fungi were obtained, 284 isolates belonging to the Aspergillus species, namely A. flavus (241), A. niger (24), A. nidulans (14) and A. fumigatus (5). Another 30 isolates were Fusarium species, identified as F. verticillioides (14), F. semitectum (10) and F. proliferatum (6). The diversity of the fungi was determined by using Shannon-Weiner Index. The diversity index indicated that A. flavus was the most abundant, recorded as 0.203.